The Effectiveness of Consuming Phoenix Dactylifera L to Increase Platelets in Dengue Hemorrhagic Fever Patients - Yuhadi, Asfani; Azizi Jayadipraja, Erwin; Sunarsih, Sunarsih (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: Based on the data from Southeast Sulawesi Provincial Health Office in 2017-2020, the prevalence of Dengue Hemorrhagic Fever has increased from year to year. The prevalence of Dengue Hemorrhagic Fever (DHF) cases for Southeast Sulawesi Province in 2017 was 32.4 per 100,000 population, increased to 38.4 per 100,000 population in 2018, increased to 63.5 per 100,000 population in 2019, and increased to 70.5 per 100,000 population in 2020. This research aimed to analyze the effectiveness of consuming Phoenix Dectylifera L, to increase platelets in DHF patients. Method: This research employed a retrospective cohort study. This research has been carried out for 30 days. The population was 176 people. The research sample consisted of 74recovered DHF patients. Meanwhile, home visits were conducted to observe the consumption of Phoenix Dectylifera L. The sampling technique was simple random sampling. The data was processed using the Data Normality Test (Kolmogorov Smirnov Test) and Anova Test. Result: The results of this research showed that the value 0.000 of consuming Phoenix Dectylifera L, to increase platelets in Dengue Hemorrhagic Fever (DHF) patients with 6 (six) days of treatment. Conclusion: There is an effect between consuming and not consuming Phoenix Dectylifera L, to increase platelets in Dengue Hemorrhagic Fever (DHF) patients.